Innovative Technological Projects of Niko and Giorgi Nikoladze in Georgia - Gochitashvili, Lali; Dvali, Tornike (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
The names of Niko Nikoladze and his son Giorgi Nikoladze hold a distinguished place alongside our renowned ancestors. It is rare to fifind a family as multi-talented, patriotic, entrepreneurial, and exemplary as father and son Niko and Giorgi Nikoladze, not just in our country, but worldwide. The equally talented children of the brilliant father continued and expanded upon their father’s ideas, contributing signifificantly to their homeland and Georgian industry. The prominent Georgians Niko and Giorgi were blessed with diverse talents, deeply European-minded, and astute businessmen. They imported modern innovations and technologies from Europe to Georgia, adapting them to local conditions and disseminating them among the populace for the country’s benefifit. Their contributions spanned science, engineering, construction, agriculture, metallurgy, railways, transportation, banking, electrifification, educational reforms, sports, mathematics, and the introduction of Georgian terminology. They even pioneered the fifirst calculating machine and numerous other innovations that greatly benefifited the country. Their achievements are countless, but one thing stands out— they possessed an immense love for their homeland and dedicated all their talents and energy to its advancement. In Didi Jikhaishi village, the Nikoladze family estate, now a museum, exemplififies how one can live a European lifestyle in a village setting. The authors of this work fifirmly believe that it is crucial for our country’s future generations to delve deeper into the legacy of Niko and Giorgi Nikoladze. As exceptionally talented, innovative, and fifiercely patriotic Georgians, their technological projects deserve special attention and widespread dissemination. By promoting their accomplishments and utilizing their works, we can pave the way for Georgia’s European future.